2021
DOI: 10.3389/fmats.2021.716967
|View full text |Cite
|
Sign up to set email alerts
|

Physical Simulation Based on Dynamic Transformation Under Hot Plate Rolling of a Nb-Microalloyed Steel

Abstract: In this work, the presence of dynamically formed ferrite above the Ae3 temperature during the physical simulation of hot rolling was presented. This unusual metallurgical process is known as dynamic transformation (DT). The metastable ferrite phase undergoes a reverse transformation when the temperature is held above the Ae3 by means of a diffusion process. These phenomena affect the rolling load during high-temperature plate rolling. Therefore, a linepipe X70 steel was studied under plate rolling with two-pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The first observations of the dynamic transformation were reported in the patent registered in the 1980s [1], who performed large deformations in common C-Mn steels at approximately the Ar 3 temperature and then rapidly quenched, the final microstructure consisted of 70% or more of equiaxed ferrite grains with a size of 4 µm or less. In later works [2][3][4][5][6][7][8], the dynamic transformation was also observed at temperatures above the Ae 3 in plain carbon steels, the combination of large strains and multiple passes conducted to ultrafine grains of ferrite of around 2 µm. Extensive research has been carried out after the pioneering work of Yada and co-workers and numerous papers have been published mainly in the last two decades.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The first observations of the dynamic transformation were reported in the patent registered in the 1980s [1], who performed large deformations in common C-Mn steels at approximately the Ar 3 temperature and then rapidly quenched, the final microstructure consisted of 70% or more of equiaxed ferrite grains with a size of 4 µm or less. In later works [2][3][4][5][6][7][8], the dynamic transformation was also observed at temperatures above the Ae 3 in plain carbon steels, the combination of large strains and multiple passes conducted to ultrafine grains of ferrite of around 2 µm. Extensive research has been carried out after the pioneering work of Yada and co-workers and numerous papers have been published mainly in the last two decades.…”
Section: Introductionmentioning
confidence: 95%
“…One of the most polemic topics has been the transformation mechanism of the dynamic ferrite, at least four different approaches [4][5][6][7][8][9][10][11][12][13][14][15] can be found in the literature attempting to explain the transformation path. One of the most accepted interpretations of the transformation mechanisms was proposed by [16], who carried out torsion tests above the Ae 3 temperature at strains from 0.5 to 2 in a steel containing 0.09%C-1.3%Mn-0.02%Si-0.036%Nb.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of performed roughing rolling in this simulation test was to provide uniform grain size distribution as well as fully recrystallized microstructure before the simulation of finish rolling. It was found that after two passes and subsequent full SRX the influence of the prior austenite grains can be neglected [3,22,23]. It could be observed that the shape of stress-strain curves for the 1 st pass of finish rolling corresponds to the shape of a stress-strain curve for fully recrystallized conditions [13,16].…”
Section: Discusionmentioning
confidence: 99%
“…The most commonly used methods for the physical modelling of rolling processes are the compression test [ 5 , 6 , 7 , 8 , 9 ] and the torsion test [ 10 , 11 , 12 , 13 , 14 ]. These methods, despite the dynamic development of the laboratory equipment, have some limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the works published so far on the physical modelling of real technological processes in torsion tests refer to the rolling of sheet metal bars [ 12 , 22 , 23 , 24 , 25 ], stepped shafts [ 26 ], or service pipes [ 10 ]. Therefore, it is reasonable to conduct research on solving problems related to the physical modelling of wire rod rolling processes in modern rolling mills, which are characterized by high linear velocities of the rolled strand with the use of modern torsion plastometers, enabling testing of the variable strain state.…”
Section: Introductionmentioning
confidence: 99%